7/9=1/3t

Simple and best practice solution for 7/9=1/3t equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7/9=1/3t equation:


t in (-oo:+oo)

7/9 = (1/3)*t // - (1/3)*t

7/9-((1/3)*t) = 0

(-1/3)*t+7/9 = 0

7/9-1/3*t = 0 // - 7/9

-1/3*t = -7/9 // : -1/3

t = -7/9/(-1/3)

t = 7/3

t = 7/3

See similar equations:

| (y-5)=4y-9 | | Y-7/8=-15/17 | | log(50x+250)-log=2 | | 4x-14=8x-47-(3x-14) | | x+16=2x-13 | | 3e=3-4 | | 8x^2-7=-5-2 | | 2x+84=10 | | 7e-41=31 | | 16x+9y=214 | | 516=42 | | F(y-5)=4y-9 | | Y=5+0.4(X+30)+-0.03(X+30)(X+20)+(X+30)(X+20)X+(X+30)(X+20)X(X+-10) | | (3w-8)4(2w+3)= | | =5+0.4(X+30)+-0.03(X+30)(X+20)+(X+30)(X+20)X+(X+30)(X+20)X(X+-10) | | -12=5v+8 | | 35=8-9w | | -4b+9=5-4 | | 12=9=(4/9m)-(1/9m) | | 83X+36Y-2916=0 | | log_(a)49=(2)/(3) | | (-5+4i)-(5+4i)= | | -4+3s=-1 | | h-/7.8=2 | | 3x+15+(11x-5)=94 | | 2X+2X-(4X-1-9X)=6X-1 | | 6x+3x+x=240 | | y/7=3/28 | | 1/2(64-6×9) | | -7(x+6)+5(2x+1)=0 | | 3x^2-8=7-2x^2 | | 9x-15=44 |

Equations solver categories